Segmental lichen planus pigmentosus. - Milano, A. (European Journal of Pediatric Dermatology, 2018)
Lichen planus pigmentosus, described for the first time in India, is more common in subjects with a dark phototype. It is characterized by hyperpigmented macules preceded or not by papules, it is scarcely itchy and does not affect the scalp, nails and mucous membranes; lichen planus pigmentosus has been reported in photoexposed locations but has also been described in covered sites, especially in folds (1). The disease begins as in our case discreetly and then extends slowly and progressively; it can last even decades. Topical immunosuppressive therapy with corticosteroids and tacrolimus is not very effective. In addition to the diffuse form, segmental forms have exceptionally been described: some of these cases appear to have a blaschkoid distribution and manifest themselves as superimposed forms to a widespread disease (2), while the distribution of other cases is neither blaschkoid nor zosteriform.